A practical pCO2 estimation and carbonate dynamics at an event of hypoxic water upwelling in Tokyo Bay - Endo, Masanori; Zhao, Yue; Nakamura, Wataru; Sasaki, Jun (Frontiers in Marine Science, 2023)
Urban bays have been considered to have a high CO2 absorption function due to the high nutrient load and resultant primary production. It is expected to enhance the function by promoting a blue carbon policy co-beneficial with strengthening ecosystem services such as fisheries. Estimates of CO2 absorption in urban bays have been based mostly on fragmentary information from shipboard observations, and an evaluation based on continuous observation of water quality is necessary considering the large spatiotemporal variability of such bay environment. In particular, Tokyo Bay has a specific feature of water pollution problem of hypoxia and anoxia leading to emitting high CO2. Bottom hypoxic and anoxic waters develop from early summer to autumn in the central part of the bay and enclosed areas such as navigation channels and borrow pits. It is known that pCO2 becomes very high in these waters, and their upwelling (called blue tide in the bay from the discoloration of the sea surface) is thought to cause high CO2 emissions; however, the actual situation is unknown. We developed a practical method for continuous estimation of pCO2 by appropriately combining continuous observation of water quality using sensors and measurements of carbonate parameters by water sampling. The results show that a highly reproducible and practical method for continuous estimation of pCO2 was possible by combining in situ salinity and pH meters and the total alkalinity and calc. pH measured by a total alkalinity titrator for water samples. This method was then applied to the duration of blue tide that occurred in the head of the bay in the summer and autumn of 2021. The pCO2 in the surface water was found to increase significantly and exceed 2000 µatm due to the upwelling of anoxic bottom water containing high pCO2. Mean CO2 emissions of approximately +2150 and +1540 µmol m-2 h-1 were observed at two stations during the upwelling period. The mean values rose to +2390 and +2190 µmol m-2h-1 with the blue tide and lowered to +810 and +1120 µmol m-2 h-1 without it, suggesting that high CO2 emissions may occur due to upwelling, especially with blue tides.